Consumption of ultraprocessed food and the role of schools and the family in the food re-education of school adolescents (Research, Society and Development, 2021)
This article aimed to present, analyze and discuss data on the food consumption of adolescent schoolchildren and their sources of information about health and nutrition and highlight the importance of healthy eating and the process of dietary re-education of adolescents through schools and of their families. For this, bibliographical and field research were carried out, with data collection and analysis in a cross-sectional study with 67 schoolchildren aged between 15 and 18 years old from a full-time public high school. A validated questionnaire containing information on food consumption and sources of information on health and nutrition was applied. The research showed that 59.16% of the students surveyed never or rarely eat fresh food, while 43.86% eat ultra-processed food at least two to four times a week. This is worrying, as the lack of adequate consumption of fresh foods, combined with the high consumption of ultra-processed foods, is a risk factor for the onset of non-transmissible chronic diseases. Finally, the importance of parents and the school as an information source on health and nutrition was highlighted, as 68.09% of those aware of good nutrition obtained information at home and 40.43% at school. New research and public policies aimed at Food and Nutrition Education are recommended, which guarantee the food security of this population.